Preparedness to Write Items for Nursing Education Examinations: A National Survey of Nurse Educators. Issue 2 (March 2022) - Moran, Vicki; Wade, Heather; Moore, Leigh; Israel, Heidi; Bultas, Margaret
Abstract : Background: Nursing programs in the United States primarily use multiple-choice questions to prepare students for the NCLEX. Background: Nursing programs in the United States primarily use multiple-choice questions to prepare students for the NCLEX. Currently, the optional next-generation NCLEX is testing the validity and reliability of situational case studies. Purpose: The purpose of this study was to investigate the preparedness and confidence of nurse educators in writing NCLEX-style questions. Methods: A descriptive survey design with snowball sampling was used to collect the data and was sent to 1550 deans/directors/coordinators of publicly available email addresses of accredited schools of nursing. Results: A total of 300 participants completed the survey from 44 states. When asked about confidence in writing NCLEX-style items, those who received formal education or training reported being somewhat confident (51%), whereas those who did not reported ambivalent or not confident (49%). Conclusion: Surveyed nurse educators lack confidence in writing questions and feel unprepared for the new question types instituted by the NCSBN in 2023. Nurse educators need continued education to develop and review NCLEX-style items and examinations.